SPORT POLICY INDONESIA: ELITE SPORT DEVELOPMENT - Rahadian, Adi; Ma’mun, Amung; Berliana, Berliana; Nuryadi, Nuryadi (Universitas Pendidikan Indonesia, 2021)
Elite sports success is identified as the leveling of the coaching system and the development of superior sports capable of winning in international competitions. In Indonesia, there is a coaching and development system of elite athletes (SKN Law No. 3 of 2005) which was adapted, is based on: a) developing elite facilities; b) providing funding for elite sports; c) providing training and sports science; and d) providing participation opportunities centered (Pelatnas) on international match planning. The novelty of this qualitative study is that it uses the pillars of success to measure medal achievement. Academics, professional athletes, and coaches were participants in this case study, which used observation, interviews, and record analysis for data collection. The aim of this research is to identify and analyze the key factors that influence the success of Indonesia's elite sports policy. The result of this report are the highest accomplishments at the 2018 Asian Games by successfully winning medals: 31 gold (14 gold from Pencak Silat), 24 silver, and 43 bronze, placing us in 4th position out of 45 Asian nations. Meanwhile, the findings of this study show that the achievement of coaching and development of elite sports at the 2018 Asian Games (Presidential Decree No. 95 of 2017) is managed systematically, professionally, and becomes a collective commitment that involves all of the nation's potential and power in improving the quality of elite sports achievements.